A petit telomere - A catalyst for bone marrow failure - A C Nirmala; G Madhu (Wolters Kluwer Medknow Publications, 2020)
Dyskeratosis congenita (DC) is a rare inherited disorder estimated to affect 1 in 1 million people characterized by rapidly depleting telomere length causing premature apoptosis or senescence results in progressive bone marrow failure. It is also known as Zinsser-Engman-Cole syndrome, and it was first described in 1906. The classic triads of DC include reticulated skin hyperpigmentation, nail dystrophy, and oral leukoplakia. Here, we report a case of a 20-year-old female presented with anemia symptoms and, on evaluation, diagnosed as bone marrow failure secondary to DC.